Sustainable Growth of the University of Maribor: Advancing Quality, Innovation, and Competitiveness for a Secure Future - Vovk, Ana; Presker, Robert; Meško, Gorazd; Marhl, Marko (50 let Univerze v Mariboru: Pol stoletja znanja in raziskovanja, 2025)
The University of Maribor, as a prominent higher education institution, recognizes that quality and sustainable development are intrinsically linked and essential for its long-term competitiveness and stability. This chapter provides an overview of the University of Maribor’s quality assurance mechanisms, analyses the current state, and highlights key challenges and opportunities within global higher education trends. Special attention is given to the shift from quantity to high-quality research and teaching, digital transformation, internationalization, and the university’s integration into the social and economic environment. The analysis compares the University of Maribor with other universities on global rankings and examines how it can strategically respond to growing competition and regional shifts in research. The focus is on developing sustainable models that encompass environmental, economic, social, and ethical aspects. The chapter explores how the University of Maribor, through a holistic approach and systematic quality improvement, can strengthen its role in sustainable development and contribute to a secure, innovative, and competitive society. Based on these findings, it outlines a vision for the University of Maribor’s future, emphasizing the integration of academic excellence with societal and economic challenges, interdisciplinarity, breakthrough research, and sustainable innovations as key strategies for enhancing its global recognition.